In Situ Decoration of ZnSnO3 Nanosheets on the Surface of Hollow Zn2SnO4 Octahedrons for Enhanced Solar Energy Application - Zhengdao Li; Kecheng Liu; Ruixue Sun; Chuanyun Yang; Xiaodi Liu (Nanomaterials, 2022)
Hierarchical ZnSnO3/Zn2SnO4 porous hollow octahedrons were constructed using the method of combining the acid etching process with the in situ decoration technique for photovoltaic and photocatalytic applications. The composite was used as photoanode of the dye-sensitized solar cells (DSSCs), an overall 4.31% photovoltaic conversion efficiency was obtained, nearly a 73.1% improvement over the DSSCs that used Zn2SnO4 solid octahedrons. The composite was also determined to be a high-performance photocatalyst for the removal of heavy metal ion Cr (VI) and antibiotic ciprofloxacin (CIP) in single and co-existing systems under simulated sunlight irradiation. It was remarkable that the composite displayed good reusability and stability in a co-existing system, and the simultaneous removal performance could be restored by a simple acid treatment. These improvements of solar energy utilization were ascribed to the synergetic effect of the hierarchical porous hollow morphology, the introduction of ZnSnO3 nanosheets, and the heterojunction formed between ZnSnO3 and Zn2SnO4, which could improve light harvesting capacity, expedite electron transport and charge-separation efficiencies.